Design and implementation of a low-power position monitoring and control system for on-orbit focusing - Leijie Jiang; Keyu Guo; Xin Liu; Zhenzhong Zhang (PLoS ONE, 2025)
To enable the optical remote sensing satellite to flexibly adjust the camera’s focal length for clearer imaging, a low-power position monitoring and control system suitable for space environments is designed, which is highly significant for aerospace devices with limited energy resources. A novel constant voltage drive circuit is proposed for driving the stepper motor. The differential linear driving and receiving circuit is presented to collect data from the linear encoder. By using the linear encoder to provide feedback on the current focal length, both open-loop and closed-loop focusing functions are achieved. The performances of the designed system are implemented on a field programmable gate array (FPGA) circuit board. The experimental results demonstrate that the developed system consumes approximately 1.4 W of power, has a strong load-carrying capacity, and achieves a focusing control precision of ±0.0004 mm over the entire motion range of −6 mm to +6 mm.